2008
DOI: 10.1165/rcmb.2007-0365oc
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Epithelial STAT3, IL-6 Family Cytokines, and Host Defense during Escherichia coli Pneumonia

Abstract: While signal transducer and activator of transcription (STAT) 3 signaling has been linked to multiple pathways influencing immune function and cell survival, the direct influence of this transcription factor on innate immunity and tissue homeostasis during pneumonia is unknown. Human patients with dominant-negative mutations in the Stat3 gene develop recurrent pneumonias, suggesting a role for STAT3 in pulmonary host defense. We hypothesized that alveolar epithelial STAT3 is activated by IL-6 family cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(145 citation statements)
references
References 59 publications
7
138
0
Order By: Relevance
“…Consistent with the functional plasticity of NK-22 cells, a recent study showed that LTilike cells isolated from human tonsils and cultured in IL-2 secrete IFN-γ (9). Interestingly, our results show that IL-2 also may be an important factor in promoting the secretion of LIF, a cytokine that has been shown to protect epithelial cells against bacterial infections (20). The functional deviation of NK-22 cells toward IFN-γ production is reminiscent of that of T H 17 T cells, which also can convert into IFN-γ-producing T H 1 T cells (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with the functional plasticity of NK-22 cells, a recent study showed that LTilike cells isolated from human tonsils and cultured in IL-2 secrete IFN-γ (9). Interestingly, our results show that IL-2 also may be an important factor in promoting the secretion of LIF, a cytokine that has been shown to protect epithelial cells against bacterial infections (20). The functional deviation of NK-22 cells toward IFN-γ production is reminiscent of that of T H 17 T cells, which also can convert into IFN-γ-producing T H 1 T cells (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 68%
“…We previously reported that NK-22 cells produce LIF (1), a cytokine that has been reported to protect the mucosal barriers (20). To determine whether cultured NK-22 cells produce LIF, we measured LIF released in supernatants by ELISA.…”
Section: Functional Polarization Induced By Il-1β Plus Il-7 Is Modifimentioning
confidence: 99%
“…The central role of the type I IFN in the host defense against viral infection has been well documented and is implicated in the pathogenesis of several bacterial infections (16,23,36). The many consequences of this cascade and its importance in linking the innate and adaptive immune response are the subject of numerous reviews (12,22).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of IFN-α family members was not detected. Production of IFN-β-dependent gene products was also observed: USA300 induced a 7-fold increase in Mx-1, a prototypical type I IFN antiviral effector, a 130-fold increase in IL-6, and a 4-fold increase in Lif, a gene product that is important in host defense in the lung specifically (23). Induction of these IFN-dependent gene products was significantly attenuated in the absence of SpA (Figure 1A).…”
Section: S Aureus Usa300 Activates Type I Ifn Signaling In Airway Cementioning
confidence: 93%
“…Virtually all cells bear the IL-17 receptor, which has been shown to recruit neutrophils to the lung by stimulating the production of the ELR1CXC chemokines, IL-8 or KC (a mouse homolog of IL-8) (57), and G-CSF. In addition, IL-17A seems to be important for the early and the late phase of neutrophil accumulation in the lungs (52). Furthermore, IL-17 can induce the up-regulation of other cytokines, including IL-1b and IL-6, and ICAM-1 by several types of cells (e.g., endothelial cells, epithelial cells) (57).…”
Section: Cytokinesmentioning
confidence: 99%